Legal Strength of Deeds Under the Hands of Notaries in Civil Proof - Febrihadi Suparidho; Yuni Ristanti (Universitas Muhammadiyah Palu, 2025)
A deed is a written evidence that plays an important role in proving civil cases. In practice, deeds are divided into authentic deeds and private deeds. Private deeds that are legalized by a notary often raise questions about their evidentiary power. This study aims to analyze the legal position and evidentiary power of private deeds that have been legalized by a notary in civil disputes. This study uses normative legal research and a normative legal approach with qualitative analysis sourced from primary and secondary legal materials. The results of the study indicate that legalization by a notary does not change a private deed into an authentic deed, but provides reinforcement to the date and signatures of the parties that the date and signatures on the private deed are indeed legalized before a notary. Thus, the deed has higher evidentiary power than ordinary private deeds, but is not equivalent to an authentic deed.